A ubiquitous enhancer shared by two promoters in the human aldolase A gene. - Concordet, J P (1991)
The human aldolase A gene is transcribed from three different promoters, which are all clustered within a 1.6 kbp DNA domain. Two of these, PN and PH, are ubiquitous and seem to be co-regulated in most tissues while the third one, PM, is specific to adult skeletal muscle. We investigated the sequences involved in the ubiquitous activity of the PN and PH promoters of the human aldolase A gene. Deletion analysis, performed by transient expression assays of chloramphenicol acetyltransferase reporter genes in human HepG2 hepatoma cells, indicated that PH activity results from the interaction of an upstream activating region with two distinct core promoters. The upstream activating region was able to stimulate transcription from the HSV tk promoter as efficiently as the SV40 enhancer in all cell types tested. It appears, therefore, to be a strong ubiquitous enhancer. DNAsel footprinting revealed protections covering sequences scattered along the enhancer, including Sp1 and AP1 motifs. Importantly, we found that this enhancer was also necessary to activity of the other ubiquitous promoter of the aldolase A gene, PN. These studies demonstrate that expression of the human aldolase A gene is mediated by a complex interplay of enhancer and promoter elements.